Can walking exercise programs improve health for women in menopause transition and postmenopausal? Findings from a scoping review. Issue 8 (August 2020) - Sydora, Beate C.; Turner, Cailey; Malley, Alexandra; Davenport, Margie; Yuksel, Nese; Shandro, Tami; Ross, Sue
Abstract: Objective: Our goal was to explore the range and characteristics of published papers on therapeutic walking programs for menopausal women and to identify program features that resulted in successful outcomes including reduced symptoms and improved long-term wellness. Methods: We searched biomedical and exercise-related databases for articles published up to June 1, 2017, using keywords related to menopause and walking. Data were collected into EndNote X8 reference manager to identify and remove duplicates. The final selection included all articles that studied walking as a health intervention for women in menopause transition or postmenopausal. Results: A total of 3, 244 papers were collected from the six databases. After removing duplicates and applying inclusion and exclusion criteria, 96 articles were charted, including 77 different walking programs. Walking interventions ranged from 4 weeks to 3 years with an average weekly frequency of 3.8 ± 1.8 and were applied to a variety of symptoms and their biological markers and risk factors. Overall, 91% of the programs showed a beneficial outcome in at least one menopause-related medical issue. Information on menopause-specific symptoms, especially vasomotor symptoms and sleep problems, was scarce. Conclusion: The scoping review highlights the growing interest in walking programs as therapies for menopause and related symptoms and provides evidence of their possible benefit as a wellness option for women in menopause and beyond. Further research would be recommended to establish the therapeutic value of walking programs for women with specific focus on typical menopause symptoms at different stages of menopause. N/A: Video Summary: http://links.lww.com/MENO/A587 . Abstract : Supplemental Digital Content is available in the text